2020
DOI: 10.31487/j.jso.2020.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Spondylectomy in the Treatment of Neoplastic Spinal Lesions – A Retrospective Outcome Analysis of 582 Patients Using a Patient-Level Meta-Analysis

Abstract: Background: En-bloc spondylectomy in the treatment of spinal tumors is a complex procedure with potential complications. This study aims at identifying predictors of postoperative complications, lesion recurrence and overall survival. Methods: A systematic review of the literature was conducted, and patient-level data extracted from the included studies. Multiple linear-regression models were calculated to predict the occurrence of postoperative complications, lesion recurrence and overall survival based on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…On this basis, TES has been applied more and more frequently. Since the vertebral body periosteum, anterior longitudinal ligament, ligamentum flavum, and to a lesser extend the posterior longitudinal ligament are considered barriers in the spread of vertebral tumors, an extra-lesional TES has been shown to result in superior oncologic outcome [ 7 ]. However, at the same time, the difficulty of the operation and the requirement of the operative experience are also quite high, which is the reason for high incidence rates of surgery related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, TES has been applied more and more frequently. Since the vertebral body periosteum, anterior longitudinal ligament, ligamentum flavum, and to a lesser extend the posterior longitudinal ligament are considered barriers in the spread of vertebral tumors, an extra-lesional TES has been shown to result in superior oncologic outcome [ 7 ]. However, at the same time, the difficulty of the operation and the requirement of the operative experience are also quite high, which is the reason for high incidence rates of surgery related complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, the difficulty of the operation and the requirement of the operative experience are also quite high, which is the reason for high incidence rates of surgery related complications. Some researchers found that the complication rate was not charged by tumor extension or tumor etiology [ 7 ], indicating that the operator's subjective awareness played a decisive role in the outcome of the surgery. The difficulty of TES lies in the accurate cognition of tumor size and surrounding important anatomical structures.…”
Section: Discussionmentioning
confidence: 99%